ABOUT A CLASS OF THREE-DIMENSIONAL SUBMANIFOLDS IN AFFINE SPACE A^6 - Arabyan, O.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
Three-dimensional submanifolds in affine space A^6 have been studied by the method of exterior forms. It is proved that the structure of total space induces a special type of affine connection on this submanifold. The structure equations of this submanifold have been found.